A Genetic Multimutation Model of Autism Spectrum Disorder Fits Disparate Twin Concordance Data from the USA and Canada. (4th March 2015) - Kramer, Ivan; Lipkin, Paul H.; Marvin, Alison R.; Law, Paul A.
Abstract : Whether autism spectrum disorder (ASD) is caused by genetics, environmental factors, or a combination of both is still being debated today. To help resolve this issue, a genetic multimutation model of ASD development was applied to a wide variety of age-of-onset data from the USA and Canada, and the model is shown to fit all the data. Included in this analysis is new, updated data from the Interactive Autism Network (IAN) of the Kennedy Krieger Institute in Baltimore, Maryland. We find that the age-of-onset distribution for males and females is identical, suggesting that ASD may be an autosomal disorder. The ASD monozygote concordance rate in twin data predicted by the genetic multimutation model is shown to be compatible with the observed rates. If ASD is caused entirely by genetics, then the ASD concordance rate of a cohort of monozygote twins should approach 100% as the youngest pair of twins in the cohort passes 10 years of age, a prediction that constitutes a critical test of the genetic hypothesis. Thus, by measuring the ASD concordance rate as a cohort of monozygote twins age, the hypothesis that this disorder is caused entirely by genetic mutations can be tested.